Physician staffed emergency medical service for children: a retrospective population-based registry cohort study in Odense region, Southern Denmark - Morten Føhrby Overgaard; Anssi Heino; Sofie Allerød Andersen; Owain Thomas; Johan Holmén; Søren Mikkelsen (BMJ PUBLISHING GROUP, 2025)
Objectives The aim of this study is to determine diagnostic patterns in the prehospital paediatric population, age distribution, the level of monitoring and the treatment initiated in the prehospital paediatric case. Hypothesis was that advanced prehospital interventions are rare in the paediatric patient population.
Setting We performed a retrospective population-based registry cohort study of children attended by a physician-staffed emergency medical service (EMS) unit (P-EMS), in the Odense area of Denmark during a 10-year study period.
Participants We screened 44 882 EMS contacts and included 5043 children. Patient characteristics, monitoring and interventions performed by the P-EMS crews were determined.
Results We found that paediatric patients were a minority among patients attended by P-EMS units: 11.2% (10.9 to 11.5) (95% CI) of patients were children. The majority of the children were <5 years old; one-third being <2 years old. Respiratory problems, traffic accidents and febrile seizures were the three most common dispatch codes. Oxygen supplementation, intravenous access and application of a cervical collar were the three most common interventions. Oxygen saturation and heart rate were documented in more than half of the cases, but more than one-third of the children had no vital parameters documented. Only 22% of the children had respiratory rate, saturation, heart rate and blood pressure documented. Prehospital invasive procedures such as tracheal intubation (n=74), intraosseous access (n=22) and chest drainage (n=2) were infrequently performed.
Conclusion Prehospital paediatric contacts are uncommon, more frequently involving smaller children. Monitoring or at least documentation of basic vital parameters is infrequent and may be an area for improvement. Advanced and potentially life-saving prehospital interventions provide a dilemma since these likely occur too infrequently to allow service providers to maintain their technical skills working solely in the prehospital environment.